DERIVATIONAL AND INFLECTIONAL AFFIXES IN THE SONG LYRICS ON THE PLAYLIST TODAY’S TOP HITS ON SPOTIFY - Hariman Rahmadani; Ni Made Widisanti; Sari Rejeki (Journal Albion : Journal of English Literature, Language, and Culture, 2022)
This research is aimed to describe the process of derivational and inflectional affixes in the song lyrics on the Playlist Today’s Top Hits Spotify and to analyze the most dominant and productive types of derivational and inflectional affixes on the playlist. The result of this study shows 268 words consist of derivational and inflectional affixes. Derivational affixes contain 59 words, with the process: Verb to Noun, Adjective to Noun, Adjective to Adverb, Verb to Adjective, Noun to Adjective, Noun to Verb, Verb to Verb, Adjective to Adjective, and Noun to Noun. Inflectional affixes consist of 209 words, with the process: -s or –es plural, -ing (progressive), -s third singular person, -ed past tense, -er (comparative), -est (superlative), -en (past participle), and ‘s (possessive). The most dominant and productive types of derivational and inflectional affixes are derivational suffixes and inflectional suffixes. Comparing the affixation process derivationally and inflectionally, the inflectional affix process is the most productive in the process of affixation.Keywords: Derivational; inflectional; affix; song lyrics.